Occupational therapy treatment time during inpatient traumatic spinal cord injury rehabilitation: A retrospective study from a tertiary center in Riyadh - Faisal Konbaz; Khalid Alsheik; Yazeed Timraz; Aishah Alsharif; Teif Almohimeed; Fatimah Othman (Journal of Spine Practice)
Background: Occupational therapy (OT) is a part of the rehabilitation process which facilitates and enables individuals with spinal cord injuries (SCI) to be as independent as possible in their activities of daily living (ADLs). Little is known about the OT treatment plan and the duration of the selected treatment intervention during SCI rehabilitation. This study aims to describe the duration of OT treatment that patients with SCI Received during their inpatient rehabilitation stay.